Overcoming invisibility: the acknowledgement of home-based businesses - Salusse, Marcus Alexandre Yshikawa (2018)
This thesis is a collection of three essays analysing the significance and characteristics of homebased businesses (HBBs) and the effect of individual and firm level conditions on HBBs performance. Home-based businesses are a phenomenon that can bring new light into a widespread forms of entrepreneurial activity, with contributions to the entrepreneurial resources and perceptions literature. These studies will allow us to explore, from different perspectives, the extent to which the HBBs characteristics differentiate from traditional onsite businesses and how individual and firm level attributes affect HBBs performance. The first study contain a systematic review of the literature, aimed at identifying the main variables expected to differentiate HBBs from non-HBBs and influence HBBs performance. The second study describes main characteristics and significance of HBBs, while the third develops a configurational typology of high and low performance HBBs.